A Locomotor Innovation Enables Water-Land Transition in a Marine Fish - Hsieh, Shi-Tong Tonia (PLOS ONE, 2010)
Background Morphological innovations that significantly enhance performance capacity may enable exploitation of new resources and invasion of new ecological niches. The invasion of land from the aquatic realm requires dramatic structural and physiological modifications to permit survival in a gravity-dominated, aerial environment. Most fishes are obligatorily aquatic, with amphibious fishes typically making slow-moving and short forays on to land. Methodology/Principal Findings Here I describe the behaviors and movements of a little known marine fish that moves extraordinarily rapidly on land. I found that the Pacific leaping blenny, Alticus arnoldorum, employs a tail-twisting movement on land, previously unreported in fishes. Focal point behavioral observations of Alticus show that they have largely abandoned the marine realm, feed and reproduce on land, and even defend terrestrial territories. Comparisons of these blennies' terrestrial kinematic and kinetic (i.e., force) measurements with those of less terrestrial sister genera show A. arnoldorum move with greater stability and locomotor control, and can move away more rapidly from impending threats. Conclusions/Significance My results demonstrate that axial tail twisting serves as a key innovation enabling invasion of a novel marine niche. This paper highlights the potential of using this system to address general evolutionary questions about water-land transitions and niche invasions.